The international clinical trials registry platform (ICTRP): data integrity and the trends in clinical trials, diseases, and drugs - Namiot, Eugenia D.; Smirnovová, Diana; Sokolov, Aleksandr V.; Chubarev, Vladimir N.; Tarasov, Vadim V.; Schiöth, Helgi B. (Frontiers in Pharmacology, 2023)
The International Clinical Trials Registry Platform (ICTRP) was created to consolidate global clinical trial registries, with the aim of providing information for research and analysis purposes. Here we present a methodology to facilitate large-scale integrity analysis of the data through data preparation, curation, and filtering. We propose a straightforward algorithm to eliminate hidden duplicates from the clinical trial data. Moreover, we utilized the ICTRP platform, as well as the DrugBank and NIH DIP databases, to identify trends and differences between ClinicalTrials.gov and non-ClinicalTrials.gov registries. We found using our new approach that 0.5% of all identified trials were hidden duplicates, primarily originating from the non-ClinicalTrials.gov database EUCTR, which had 82.9% of all hidden duplicates. Overall the number of hidden duplicates in the ICTRP was appears to be decreasing. Additionally, it was interesting to note that some non-drug words appeared frequently in certain subsets of the ICTRP. In total we analyzed 689 793 trials that were registered on the ICTRP between 1990 and 2020, and found that this number was higher than that of ClinicalTrials.gov, which contained 362 500 studies as of the end of 2020. Of these trials, 478 345 were classified as interventional. Using the DrugBank database, we identified 225 857 agents, with 4 865 being unique, while the NIH database identified 173 473 agents, with 2 633 being unique drugs. The European Union Clinical Trials Registry (EUCTR) had the largest number of trials identified in ICTRP, followed by the the Clinical Trials Registry India (CTRI), the Iranian Registry of Clinical Trials (IRCT), the Chinese Clinical Trial Registry (CHiCTR) and the International Traditional Medicine Clinical Trials Registry (ISRCTN). CHiCTR stood out with a noticeable increase in trial registration starting around 2015, while CTRI was the second most rapidly growing database, starting its rise in 2016. In conclusion, this study highlights both the strengths and weaknesses of using the ICTRP as a data source for analyzing trends in clinical trials, and emphasizes the value of utilizing multiple registries for a more comprehensive analysis.